NUTRITIONAL VALUE OF TRADITIONAL WILD VEGETABLES USED BY THE KINNAURA TRIBALS OF HIMACHAL PRADESH, INDIA. - GEETA,; RICHA,; M.L. SHARMA, (International Journal of Pharma and Bio Sciences, 2015)
After interacting with local people of Kinnaur, nine wild vegetables viz. Allium wallichii, Crambe kotschyana, Diplezium esculentum , Eremurus himalaicus, Fagopyrum tataricum, Lepyrodiclis holosteoides, Rorippa nasturtium- aquaticum , Silene vulgaris, Urtica dioca were selected for proximate composition analysis, including mineral and vitamin content. Young green shoot tips and leaves of Crambe kotschyana are very rich in proteins (36.68 mg/100gm); Rorippa nasturtium- aquaticum in minerals (16.76 mg/100gm ); and Diplezium esculentum in vitamin C (56.87mg/100gm) and fiber (6.89mg/100gm). The range of nutrients present in these vegetables is comparable with the commonly used cultivated green leafy vegetables. Infact, the protein (4.20- 36.28mg/100gm) and iron (3- 44.2 mg/100gm) content is much higher than that most of the cultivated vegetables. The present study should be helpful to educate the local youth about the nutritional value of this plant wealth of the region and create an interest in its conservation, collection and sustainable consumption.